The content and direction of the high-performance hockey players’ technical training - Rotenberg R.B. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to describing a possible model of technical training for high-performance hockey players, namely, the structure, components, and principles of managing the training process. Methods and structure of the study. To collect data on technical training of high-performance hockey players, the following methods were used: pedagogical observation, video and expert analysis of competition activities. Results and conclusions. This study is based on video analysis of competition activities of high-performance hockey players. The focus of the analysis is put on the description of competition technical skills in terms of the complex conditions for performing the hockey competition exercise. The analysis of various aspects of competition skills in hockey is foregrounded as the key to managing the game performance. The study identified the most important components in the content and structure of technical readiness of high-performance hockey players and formulated the principles of improving hockey players’ technical skills.